Avaliação tecnológica e biológica de formulações promissoras para o tratamento da malária - Maciel, Tamara Ramos (2024)
Malaria is an inflammatory disease that affects millions of people worldwide. Our research group has been devoted to the development and evaluation of nanocapsules containing antimalarial drugs for disease treatment, yielding promising outcomes. Nanoencapsulation of quinine has demonstrated increased survival rates in P. berghei- infected animals, extended residence time of quinine in blood circulation, and mitigated adverse effects on male and female reproductive systems compared to its free form. Cationic nanocapsules coated with Eudragit®RS100 (EUD) and containing quinine exhibited enhanced survival rates and greater parasitemia suppression. Combining quinine with curcumin in nanocapsules reduced parasitemia in vitro and minimized toxic effects on C. elegans. Thus, our overarching objective was to develop and characterize polymeric nanocapsule formulations and assess their in vivo biological and toxicological activity for malaria treatment. Considering potential combination therapy, drug interactions were evaluated through pharmacokinetic modeling based on chloroquine (CQ) and colchicine (CC) physiology. As both drugs undergo CYP450 metabolism, particularly by CYP3A4, we investigated their interactions, finding no significant interactions for both enzymes. Subsequently, nanocapsules for co- encapsulation of CQ and CC were developed. An analytical methodology for drug quantification was established, proving selective, reproducible, linear, precise, accurate, and robust. Thermal compatibility between drugs and excipients for nanocapsule suspension preparation was confirmed, followed by the development and characterization of stable formulations exhibiting typical EUD characteristics over 90 days. In vitro drug release followed a bi-exponential model. The CQ and CC formulations showed no acute toxicity in vivo. Further, cationic nanocapsules containing CC were developed and characterized using factor analysis, yielding eight formulations, with NC7 selected for biological evaluation. Pharmacokinetics in female Wistar rats demonstrated improved parameters compared to free drugs, such as increased plasma and blood exposure, reduced elimination, and prolonged retention in the central compartment, crucial for prolonged parasite exposure. Collectively, these findings highlight the technological and biological potential of CC-containing cationic nanocapsule suspensions.